Ionic liquid-assisted synthesis of Bi12TiO20 nanostructures and their visible-light photocatalytic performance. (23rd August 2016) - Ren, J. F.; Li, J. Z.; Song, Z. W.
Abstract: Bi12 TiO20 nanostructures were prepared in an ionic liquid (1-methyl-3-butyl imidazole bromide, [BMIM]Br)–water solvent mixture through a hydrothermal process. The effect of ionic liquid on the morphology, optical and photocatalytic properties of the products was investigated. By slightly adjusting the amount of [BMIM]Br, Bi12 TiO20 nanoparticles, nanorods and raft-like ones with different crystallinities, surface areas and bandgap energies could be obtained. In these three kinds of morphologies, Bi12 TiO20 nanorods with average diameter of 20–30 nm and length of 100–270 nm demonstrate the highest photocatalytic performance for its degradation of methylene orange under visible-light irradiation. The results suggest that the presence of ionic liquid in the synthetic system plays a key role in tuning the phase composition, the shape, size and purity of Bi12 TiO20 powders, and hence affects their morphology-associated optical adsorption ability and photocatalytic activity.